An Empirical Cross-Cultural Study of Moral Judgment Development in Mainland China - Zhang, Qian; Thoma, Stephen J. (ETHICS IN PROGRESS, 2016)
The Chinese version of Rest’s Defining Issues Test II was administered to 113 subjects in Mainland China (n=113, average age=34.7). The scores on development of moral judgment were compared with those of the online mega sample of American participants from 2011 to 2014. Results are as followings: 1. Chinese participants show the same pattern with Americans by both sex and education. 2. Chinese participants show different pattern from Americans by religious orthodoxy and humanitarian. 3. Chinese participants score higher in meaningless items than Americans. 4. Chinese participants score higher in stage 3 while Americans score higher in stage 4. The authors draw the conclusions as follows: with Chinese participants, 1. There is a significant relationship between education and moral judgment developmental index scores. 2. There is also a significant relationship between sex and moral judgment developmental index scores. 3. There shows no significant relationship between religious orthodoxy and moral judgment developmental index scores. 4. It is more difficult for them to tell the meaningless items in DIT2. 5. Since Chinese culture thinks less of laws and norms, Chinese participants favour personal interest schema more than maintaining norms schema.